2021
DOI: 10.1016/j.microc.2021.105925
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electrochemical detection of azithromycin and hydroxychloroquine based on VS2 QDs embedded N, S @graphene aerogel/cCNTs 3D nanostructure

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…From this calculation, it was found that two electrons were involved in the HCQ oxidation under acidic pH conditions ( Figure 3 ). In fact, the value of E° confirms the results reported by Mahnashi et al [ 40 ], Decoro et al [ 31 ], Khoobi et al [ 41 ], and Arguelho et al [ 11 ] which have suggested that the electrooxidation of HCQ involved the nitrogen atom of the alkylamino side chain and the N-heterocyclic nitrogen of the aminoquinoline moiety of hydroxychloroquine, respectively ( Figure 3 ). E° was obtained from the slope of E pa versus ln v (assuming α = 0.5).…”
Section: Resultssupporting
confidence: 89%
“…From this calculation, it was found that two electrons were involved in the HCQ oxidation under acidic pH conditions ( Figure 3 ). In fact, the value of E° confirms the results reported by Mahnashi et al [ 40 ], Decoro et al [ 31 ], Khoobi et al [ 41 ], and Arguelho et al [ 11 ] which have suggested that the electrooxidation of HCQ involved the nitrogen atom of the alkylamino side chain and the N-heterocyclic nitrogen of the aminoquinoline moiety of hydroxychloroquine, respectively ( Figure 3 ). E° was obtained from the slope of E pa versus ln v (assuming α = 0.5).…”
Section: Resultssupporting
confidence: 89%
“…The literature does not clearly report the nature of the two oxidation peaks presented. Several studies [8,13,17,18,38,39] show that the oxidation reaction of HCQ is pH-dependent. This fact makes possible some assumptions about the process from what is informed, based on the pKa values of the functional groups of the HCQ molecule.…”
Section: Electrochemical Performance Of Cnns/ementioning
confidence: 99%
“…Electrochemical sensors can be manufactured by using several materials, and in some cases, taking many steps through the synthesis of modifiers [17,18]. However, carbon paste stands out due to its ease of production, modification, and assembly on the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is vital to construct selective, sensitive, and cost-effective sensors to detect S. aureus . Electroanalytical techniques have drawn great attentions as a result of fast response, sufficient selectivity, low detection limits, simplicity, and low cost 6 12 .…”
Section: Introductionmentioning
confidence: 99%